Adeno-associated virus neutralising antibodies in type 1 diabetes mellitus - Andrzejewski, Slawomir; Murali, Aparna; Ramlogan-Steel, Charmaine; Edwards, Katie P.; Efron, Nathan; Steel, Jason C.; Layton, Christopher J. (Gene therapy, 2019)
Recombinant Adeno-associated viruses (AAVs) are an attractive vector for gene therapy delivery which may be blocked by AAV neutralising antibodies (NAbs). As Type 1 Diabetes (T1DM) is an endocrine disease of immunological origin, it is likely that NAb profiles are altered in the disease. In this study NAb to AAV2, AAV5, AAV6, and AAV8 in 72 subjects with T1DM and 45 non-diabetic patients were measured over a 4-year follow-up period. AAV2 NAb titres were significantly lower in non-diabetic subjects ( P = 0.036). The T1DM group had more AAV8 NAb activity at baseline ( P = 0.019), whilst after 4 years follow-up the T1DM group displayed developed increased AAV 5 ( P = 0.03), 6 ( P = 0.03) and 8 ( P = 0.002) activity relative to the control group, however, overall AAV5 and 8 NAb levels were very low in patients <40. AAV NAb titre activity and prevalence generally appears higher in T1DM, however, low levels of AAV 5 and 8, particular in younger adult age groups at which T1DM can be targeted, could make these attractive vectors to target the disease.